Bioelectricity Generation from Plantain Peel Waste using Saccharomyces cerevisiae in a Low-Cost Microbial Fuel Cell - Amenze Oyedoh, Eghe; Emmanuel Amechi Metuiwe; Stanley Aimhanesi Eshiemogie (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
This study investigates the potential of using plantain peel waste as a substrate in a microbial fuel cell (MFC) for bioelectricity generation. Saccharomyces cerevisiae was employed as the microbial inoculum, while kaolinite clay combined with starch was used to fabricate a cost-effective proton exchange membrane (PEM). The performance of the microbial fuel cell was monitored over a period of 13 days, during which a steady generation of electricity was observed, including current and voltage readings of 0.903 mA and 0.42 V; and 0.03 mA and 0.47 V on days 1 and 13 respectively. The maximum current density, power density, and voltage density were recorded as 1157 mA/m², 527.62 mW/m², and 289.5 V/m², respectively. The study demonstrated that plantain peel waste is a suitable substrate for electricity generation, and the clay-starch membrane functioned effectively as a proton exchange membrane, albeit with limited viability. This experiment also showcased the feasibility of creating a low-cost microbial fuel cell using locally available materials, which provides a potential avenue for sustainable and economically viable bioelectricity production to meet future electricity needs.